2015
DOI: 10.1109/tcst.2014.2371826
|View full text |Cite
|
Sign up to set email alerts
|

Control of PEMFC Air-Feed System Using Lyapunov-Based Robust and Adaptive Higher Order Sliding Mode Control

Abstract: In this brief, we present Lyapunov-based robust 1 and adaptive higher order sliding mode (HOSM) controllers 2 for the air-feed system of polymer electrolyte membrane fuel 3 cells, which is a nonlinear single-input, single-output system 4 with bounded uncertainty. The system consists of a motorized 5 compressor, which is driven at its optimal point in order to 6 minimize the internal energy consumption of the system. This 7 brief provides an experimental demonstration of the applicabil-8 ity of the recently dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Finally, by the fact that e 2 D N s 2 O N s 2 is bounded, we obtain N s 2 , which is also bounded during OE0; T 1 . From the aforementioned proof, it is clear that system (7) can be globally stabilized by controller (24). Note that controller (24) can be rewritten as (8).…”
Section: Proofmentioning
confidence: 90%
“…Finally, by the fact that e 2 D N s 2 O N s 2 is bounded, we obtain N s 2 , which is also bounded during OE0; T 1 . From the aforementioned proof, it is clear that system (7) can be globally stabilized by controller (24). Note that controller (24) can be rewritten as (8).…”
Section: Proofmentioning
confidence: 90%
“…HOSM has the ability to remove the chattering effect completely and provides higher accuracy in realization while maintaining the basic advantage of original approach. Several numbers of such controllers have been reported in the literature [34][35][36]. Among these, the second-order sliding mode controller (SOSMC) is popular due to its easy implementation.…”
Section: Second-order Sliding Mode Controller (Sosmc) Designmentioning
confidence: 99%
“…Sliding mode with homogeneity approach was also used in [7], [8], to demonstrate finite time stabilization of the arbitrary order sliding mode controllers for SISO systems [1]. A Lyapunovbased approach for arbitrary HOSMC controller design was presented in [9], [10]. In this work, it was shown that a class of homogeneous controllers that satisfies certain conditions, could be used to stabilize perturbed integrator chains.…”
Section: Introductionmentioning
confidence: 99%